(untitled) (Eurasian Journal of Ecology, 2016)
Investigation of the pregnant rat erythrocytes in the phsicoemotional stress status. It has been demonstrated in the emotional stress influence on membrane status and osmothyc stability of the pregnant rat erythrocytes. Osmothyc stability and membrane penetration in pregnant rats were changed comparatively with control rats.